Host genetic variation explains reduced protection of commercial vaccines against Piscirickettsia salmonis in Atlantic salmon - Figueroa, C; Veloso, P; Espin, Lenin; Dixon, B; Torrealba, D; Said Elalfy,Islam; Afonso López, Juan Manuel; Soto, C; Conejeros, P; Gallardo, JA (Scientific Reports, 2020)
Vaccination is a widely used control strategy to prevent Piscirickettsia salmonis causing disease in salmon farming. However, it is not known why all the currently available commercial vaccines generally fail to protect against this pathogenic bacteria. Here, we report, from two different populations, that between-family variation is a strong intrinsic factor that determines vaccine protection for this disease. While in some full-sib families, the protection added by vaccination increased the survival time in 13 days in comparison with their unvaccinated siblings; in other families, there was no added protection by vaccination or even it was slightly negative. Resistance to P. salmonis, measured as days to death, was higher in vaccinated than unvaccinated fish, but only a moderate positive genetic correlation was obtained between these traits. This disputes a previous hypothesis, that stated that both traits were fully controlled by the same genes, and challenges the use of unvaccinated fish as gold standard for evaluating and selecting fish resistant to P. salmonis, particularly if the offspring will be vaccinated. More studies are necessary to evaluate if variation in the host immune response to vaccination could explain the between-family differences in resistance observed in vaccinated fish. 1,24 4,379 Q1 Q1 SCIE